Samuel P. S. Ho y Ralph W. Huenemann, China's Open Door Policy. The Quest for Foreing Technology and Capital, Vancouver, University of British Columbia Press, 1984, pp. viii + 277. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1986)
-